Gestational diabetes and serum ferritin concentration in Iraqi pregnant women - Nadia N. Hasan (Romanian Medical Journal)
Background. A strong connection between elevated ferritin levels and diabetes incidence was noted as diabetes mellitus (DM) in pregnant women. Objective. The aim of this study was to examine the effect of elevated ferritin levels on the development of gestational diabetes mellitus GDM in early pregnancy. Materials and methods. Thirty expecting women with a gestational age of 12-16 weeks and 30 age-matched healthy pregnant women were enrolled in this study. Blood measurement of ferritin was collected in the first trimester. Glucose tolerance test was done to diagnose GDM at the period (24-28) weeks. Results. Highly significant differences in the levels of HbA1C, R.B.S, and ferritin were found between control and patients (p=0.0001), respectively. There was positive correlation in the ferritin level with HbA1c (r=9033), RBS (r=0.24) and with iron r=(0.002). Conclusion. Serum ferritin can be used as a diagnostic marker for gestational diabetes mellitus in the first and second trimesters of pregnancy, and to determine the appropriate regular supplementation and dosage relationship for both anemic and non-anemic pregnant women.